Pengaruh Variabel Celebrity Endorser Terhadap Citra Merek L’oreal (Studi Produk L’oreal Paris Total Repair di Fakultas Ekonomi dan Bisnis Universitas Brawijaya) - Zakiya Sabdosih; Djumillah Hadiwidjoyo (Jurnal Ilmiah Mahasiswa FEB, 2012)
:The use of celebrities in various advertisements is one of the effective marketing strategy to gain or maintain market share.  In recent years, using celebrity endorsers has become more and more common. The use of celebrities as endorsers is expected to give a positive association to the link between celebrities and products offered.Celebrity endorsement is one of the most popular methods of promotion in the worldwhich take important part of a product marketing campaign.  Furthermore,  influence of celebrity endorser is formed by several factors that can be found  from the celebrity endorser himself, these factors are trustworthiness, expertise, attractiveness, respect and similarity. The purpose of this research  is to unveil the positive effects that celebrity endorsement has on a brand’s image and to discover the most important factors that an effective endorsement relies on.To discover the customers’ response towards the product and brand image that celebrities are endorsing, five variabel will be analyzed in this research.The intention for choosing this topic was to see how effective using a celebrity to endorse hair productin Brawijaya University.Keywords : Celebrity endorser, trustworthiness, expertise, attractiveness, respect, similarity, brand image, advertising.